ALAT PEMANTAU LOKASI DAN KESEHATAN LANSIA BERBASIS INTERNET OF THINGS - Delima Ayu Anugrah; Herlambang Saputra; Ica Admirani (Teknik Komputer Politeknik Negeri Sriwijaya, 2026)
The elderly population in Indonesia increases yearly, along with health risks and potential disorientation due to cognitive decline. Therefore, a wearable, remotely accessible device is needed to monitor both location and vital signs. This study aims to design an IoT-based wearable device that monitors body temperature, heart rate, and oxygen saturation of elderly individuals, along with real-time location tracking via the Telegram application. The device integrates MLX90614, MAX30100, and GPS NEO-6M sensors controlled by a Wemos D1 Mini microcontroller connected through a 4G modem. Data is sent automatically every three hours and can also be requested manually using the kondisi